Tactics of treatment of the inflow varico-thrombophlebitis - S. S. Filip; V. V. Rusyn; І. І. Hadzheha (Клінічна хірургія, 2020)
Objective. To substantiate the indications for surgical treatment of the inflow thrombophlebitis, depending on state of venous hemodynamics in the large subcutaneous vein basin.